The Legal Politics of Establishing the Asset Seizure Law: A New Strategic Paradigm for Combating Corruption and Economic Crimes in Indonesia - Khaliq, Muhammad Nur; Fatimah, Siti (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study examines the legal politics underlying the formation of the Asset Seizure Law in Indonesia as a strategic initiative to combat corruption and other economic crimes. Employing library research methods and a juridical-normative approach, the study explores the background, legal concepts, and the impact of legal politics on the regulation’s development. The primary focus is a comprehensive analysis of the paradigm shift from a criminal to a civil approach, emphasizing the application of the principle of non-conviction-based asset forfeiture to expedite asset Seizure without requiring a criminal conviction. The findings indicate that this law addresses technical and administrative challenges in asset Seizure while balancing state interests with the protection of individual rights. With transparent and accountable regulations, the Asset Seizure Law is anticipated to enhance the effectiveness of law enforcement and bolster public trust in Indonesia’s legal system.